Association of famine exposure and the serum calcium level in healthy Chinese adults - Yang, Yu-ying; Zhang, Deng; Ma, Ling-ying; Hou, Yan-fang; Bi, Yu-fang; Xu, Yu; Xu, Min; Zhao, Hong-yan; Sun, Li-hao; Tao, Bei; Liu, Jian-min (Frontiers in Endocrinology, 2022)
Objective Famine exposure and higher serum calcium levels are related with increased risk of many disorders, including Alzheimer’s disease, atherosclerosis, diabetes, and osteoporosis. Whether famine exposure has any effect on serum calcium level is unclear. Besides, the normal reference range of serum calcium is variable among different populations. Our aims are 1) determining the reference interval of calcium in Chinese adults; 2) exploring its relationship with famine exposure. Methods Data in this study was from a cross-sectional study of the epidemiologic investigation carried out during March-August 2010 in Jiading district, Shanghai, China. Nine thousand and two hundred eleven participants with estimated glomerular filtration rate (eGFR) ≥60ml/min/1.73m2 were involved to calculate reference interval of total calcium from 10569 participants aged 40 years or older. The analysis of famine exposure was conducted in 9315 participants with complete serum biochemical data and birth year information. Results After rejecting outliers, the 95% reference interval of total serum calcium was 2.122 2.518 mmol/L. The equation of albumin-adjusted calcium was: Total calcium + 0.019* (49-Albumin), with a 95% reference interval of 2.151 2.500 mmol/L. Compared to the age-balanced control group, there was an increased risk of being at the upper quartile of total serum calcium (OR=1.350, 95%CI=1.199-1.521) and albumin-adjusted calcium (OR=1.381, 95%CI=1.234-1.544) in subjects experienced famine exposure in childhood. Females were more vulnerable to this impact (OR= 1.621, 95%CI= 1.396-1.883 for total serum calcium; OR=1.722, 95%CI= 1.497-1.980 for albumin-adjusted calcium). Conclusions Famine exposure is an important environmental factor associated with the changes in circulating calcium concentrations, the newly established serum calcium normal range and albumin-adjusted calcium equation, together with the history of childhood famine exposure, might be useful in identifying subjects with abnormal calcium homeostasis and related diseases, especially in females.